Trajectory-tracking control of Mecanum-wheeled omnidirectional mobile robots using adaptive integral terminal sliding mode. (December 2021) - Sun, Zhe; Hu, Shujie; He, Defeng; Zhu, Wei; Xie, Hao; Zheng, Jinchuan
Abstract: Mecanum-wheeled omnidirectional mobile robot (MWOMR) is playing an increasingly significant role in modern transportation and industry due to its high flexibility and maneuverability. This paper presents an adaptive integral terminal sliding mode (AITSM) control algorithm for an MWOMR trajectory-tracking task. Initially, a four-inputs-three-outputs kinematic-and-dynamic model is identified to describe the MWOMR's trajectory-tracking behavior. Subsequently, an AITSM controller is designed for the MWOMR, where the stability of control system is theoretically validated by means of Lyapunov. For comparison, a conventional sliding mode (CSM) controller and a nonsingular terminal sliding mode (NTSM) controller are also designed as benchmarks. Finally, simulations are executed to test the performance of proposed control laws in various scenarios. The simulation results substantiate that our AITSM control strategy is an effective solution to the MWOMR trajectory-tracking problem, which exhibits remarkable superiority in terms of tracking precision and control robustness compared with the CSM and NTSM control.